2019
DOI: 10.1155/2019/8323592
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Leukemia Stem Cell-Niche Dynamics: A New Challenge in AML Treatment

Abstract: One of the most urgent needs in AML is to improve the disease cure rate as relapse still occurs in 60–80% of patients. Recent evidence suggests that dismal clinical outcomes may be improved by a better definition of the tight interaction between the AML cell population and the bone marrow (BM) microenvironment (“the niche”); the latter has been progressively highlighted to have an active role in the disease process. It has now been well established that the leukemic population may misinterpret niche-derived si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 122 publications
(137 reference statements)
0
18
0
Order By: Relevance
“…As a result, it is suggested that the best treatment strategy is to prevent AML-induced hypoxia leading to arteriole loss in the endosteum, so as to prevent the development of AML due to the hypoxia area (the real “shelter” of LSCs) derived from BM niche. 26 Some studies have made efforts to this end. For example, it was found that the ECs of AML mice model produced more nitric oxide, and the recovery of normal vascular function in BM through nitric oxide synthetase (NOS) inhibition improved the treatment response.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, it is suggested that the best treatment strategy is to prevent AML-induced hypoxia leading to arteriole loss in the endosteum, so as to prevent the development of AML due to the hypoxia area (the real “shelter” of LSCs) derived from BM niche. 26 Some studies have made efforts to this end. For example, it was found that the ECs of AML mice model produced more nitric oxide, and the recovery of normal vascular function in BM through nitric oxide synthetase (NOS) inhibition improved the treatment response.…”
Section: Discussionmentioning
confidence: 99%
“…The crosstalk between leukemic stem/progenitor cells and bone marrow microenvironment has been highlighted as an important process for the resistance to chemotherapy and disease relapse in AML, mainly through the activation of the CXCL12/CXCR4 pathway ( Bernasconi and Borsani, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The appearance of these changes observed in the BM niche follows a specific temporal order, reflecting the AML developmental phase. The establishment of a pre-leukemic niche is followed by the development of a leukemia-permissive and lately self-reinforcing environment [ 52 ]. Some of these alterations, such as the microvessel density, the loss of nestin expression (indicator of nerve damage), and the aberrant cellular composition of the BM mesenchymal and osteoblastic compartments, have been correlated to AML clinical features, such as aggressiveness, sensitivity to treatment, and patients’ overall survival [ 47 , 48 , 49 ].…”
Section: The Role Of Lsc and The Bm Microenvironment In Amlmentioning
confidence: 99%